10 - Commentary: A Comparison of Comparisons - Patrick Manning, (Afrika Zamani, 2022)
This commentary on the articles collected in this issue confirms that they illustrate effectively the main approaches to historical comparison for Africa in recent centuries. The essay reaffirms A.I. Asiwaju's introductory statement of the crucial importance of comparative work in advancing studies of African history, and amplifies this argument by asserting that comparative and global frameworks each have their place, and that each can be employed as a tactic or strategy in historical analysis. The discussion continues with exploration of three articles that explore the rules for and results of historical comparison; three articles comparing cases that overlap and interact with each other; and three articles comparing discrete cases. The essay concludes by summarizing the ways that the comparisons, in the various studies, have clarified narratives and have documented historical processes. Overall, it appears, the articles are effective in showing how comparisons can advance understanding of what Professor Asiwaju has called 'the history of man in Africa'.